2020
DOI: 10.1002/nafm.10437
|View full text |Cite
|
Sign up to set email alerts
|

Is Bigger Better? Evaluation of Size‐Selective Predation on Age‐0 Walleye

Abstract: The success of fish stocking programs is dependent on poststocking survival. However, survival can be influenced by size‐selective mortality, where larger individuals are expected to be less vulnerable to predation. Walleye Sander vitreus is a commonly stocked sport fish, but little is known regarding the role of size‐selective predation on age‐0 Walleye (90–290 mm TL) that are stocked in the presence of various piscivores with different foraging strategies and morphological features. Our objective was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 46 publications
0
32
1
Order By: Relevance
“…As discussed earlier, current stocking practices may need to be reevaluated, especially to reduce such high predation of bloater immediately following release. Other approaches, such as staggering releases either spatially or temporally, pre‐conditioning bloater to stressors ( e.g ., predators) during rearing (Brown et al ., 2003; D'Anna et al ., 2012; Hutchinson et al ., 2012) or releasing more (or larger) bloater each stocking event (Grausgruber & Weber, 2020), may ameliorate post‐release survival and remain to be tested. Considering the past and ongoing rehabilitation efforts for stocking of lake trout throughout the Great Lakes and particularly in Lake Ontario (Muir et al ., 2012; Stewart et al ., 2017), it is unlikely that changes to predator abundance will mitigate bloater predation.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, current stocking practices may need to be reevaluated, especially to reduce such high predation of bloater immediately following release. Other approaches, such as staggering releases either spatially or temporally, pre‐conditioning bloater to stressors ( e.g ., predators) during rearing (Brown et al ., 2003; D'Anna et al ., 2012; Hutchinson et al ., 2012) or releasing more (or larger) bloater each stocking event (Grausgruber & Weber, 2020), may ameliorate post‐release survival and remain to be tested. Considering the past and ongoing rehabilitation efforts for stocking of lake trout throughout the Great Lakes and particularly in Lake Ontario (Muir et al ., 2012; Stewart et al ., 2017), it is unlikely that changes to predator abundance will mitigate bloater predation.…”
Section: Discussionmentioning
confidence: 99%
“…Boat electrofishing consisted of sampling the entire circumference of the 229‐ha area in East Okoboji Lake and the 152‐ha area in West Okoboji Lake with boat electrofishing in depths ≤3 m. Upon capture, predator total length (mm) and weight (g) were recorded, stomach contents were nonlethally collected from all captured predators via pulsed gastric lavage (Foster 1977; Waters et al 2004), and all predators received a fin clip (2016 = left pelvic fin, 2017 = top caudal fin) to estimate predator abundance. Largemouth Bass, Northern Pike, and adult Walleye can consume age‐0 Walleye between 20% and 70% of their total length (Grausgruber and Weber 2020), and a large proportion of the stocked age‐0 Walleye were ≥150 mm. Therefore, we sampled predators ≥230 mm TL to ensure that we sampled any individuals that were capable of consuming stocked age‐0 Walleye.…”
Section: Methodsmentioning
confidence: 99%
“…Walleye are stocked at a variety of sizes (e.g., fry and fingerling) with variable stocking success (Fielder 1992; Jennings and Philipp 1992; Mitzner 1992; Kampa and Hatzenbelor 2009; Weber and Weber 2020a). Several predators consume a wide size range of age‐0 Walleye (16–300 mm), including Largemouth Bass Micropterus salmoides (Freedman et al 2012; Grausgruber and Weber 2020), Smallmouth Bass Micropterus dolomieu (Johnson and Hale 1977; Liao et al 2004), Northern Pike Esox lucius (Anthony and Jorgensen 1977; Nate et al 2003; Grausgruber and Weber 2020), Muskellunge Esox masquinongy (Bozek et al 1999; Grausgruber and Weber 2020), and adult Walleye (Chevalier 1973; Liao et al 2002; Grausgruber and Weber 2020). However, prior approaches used to evaluate the effects of poststocking predation are limited by their classification of age‐0 Walleye into broad size‐classes (e.g., larval, small, medium, and large fingerlings; Santucci and Wahl 1993; Brooks et al 2002; Hoxmeier et al 2006) and by limited temporal resolution (Stein et al 1981; Santucci and Wahl 1993; Freedman et al 2012) and focus on age‐0 Walleye stocked at smaller sizes (<200 mm; Chevalier 1973; Hoxmeier et al 2006; Freedman et al 2012).…”
mentioning
confidence: 99%
“…Stocking of predatory species has been used to take advantage of and potentially control overabundant, stunted prey species ( Irwin et al 2003;Vrtiska et al 2003;Denlinger et al 2006;Wamboldt et al 2020). Stocking strategies have also been adapted to overcome reduced natural recruitment and increased predation (Fayram et al 2005;Grausgruber and Weber 2020). For example, stocking programs for Walleye Sander vitreus, Hybrid Striped Bass Morone saxatilis  Morone chrysops, and White Bass M. chrysops were implemented in Lake McConaughy, Nebraska following population declines attributed to competition following the introduction of Alewife (Porath et al 2003;Schall et al 2019;Perrion et al 2020).Stocking strategies may also require adaptation following the introduction of an invasive species (Mercado-Silva et al 2007;Feiner et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The size of stocked fish and other seasonal abiotic factors can influence stocking success. Fish size at stocking may be a large contributor to stocking success; generally larger fish have higher survival rates (Szendrey and Wahl 1996;Sutton and Ney 2001;Grausgruber and Weber 2020). Other studies have shown seasonal trends related to predator-prey relationships may be important to successful recruitment (Garvey et al 1998;Zweifel et al 2009).…”
Section: Introductionmentioning
confidence: 99%